Development of Banana Pseudostem Incorporated Nuggets from Threadfin Bream (Nemipterus japonicus) Surimi and its Quality Evaluation During Frozen Storage: Banana Pseudostem Nuggets from Threadfin Bream Surimi - Anjana, J. E.; Toms, C. Joseph; Joshy, C. G.; Sreepriya, Prakasan; George, Ninan (Fishery Technology, 2025)
The objective of this study was to evaluate the effect of banana (Musa acuminata cv. Palayam Codan, AAB group) pseudostem flour (BP) on enhancing the nutritional, biochemical, organoleptic, and microbial quality of surimi nuggets during frozen storage. Surimi nuggets were prepared from threadfin bream by incorporating BP at varying concentrations (0%, 1%, 2.5%, and 5%). The nugget formulation with the highest dietary fibre content and acceptable sensory score was identified using Response Surface Methodology (RSM). The inclusion of 5% BP in surimi nuggets (SNBP) resulted in a 2.57% increase in total dietary fibre (TDF) compared to control surimi nuggets (SN) without BP. The nuggets were subjected to quality assessments over 240 days of storage at -18 ± 2°C. The thiobarbituric acid value, peroxide value, and free fatty acid value of both SN and SNBP increased significantly (P